Design and simulation of RF-CMOS SPST switch for reconfigurable RF front-end - Soeroso, Iksannurazmi Bambang; Alam, A. H. M. Zahirul; Nordin, Anis Nurashikin (Seek Digital Library, 2014)
The consumer demands on having multifunctional wireless communication devices have driven current mobile handset to be more complex than it has ever been before. In particular, radio frequency (RF) front-end has evolved to adapt with multi-standards terminals. Thus, by having integrated switches and resonators on the same chip may be considered as a compact solution. In this paper, the design and simulation of RF-CMOS SPST switch is presented. The switch exhibits insertion loss of 1.15-dB and 1.155-dB at 850MHz and 1.125GHz respectively. On the other hand, the isolation is > 22dB in this frequency range while its P1dB is > 20dBm. Pre and post layout of the switch is included in this paper to observe the effect of parasitic capacitance in the layout design.